GENDER CONSTRUCTION IN THE LEGEND OF THE GREEN PRINCESS IN SIBERAYA VILLAGE, KARO REGENCY AND ITS RELEVANCE AS A TEACHING MATERIAL IN SMP NEGERI 8 MEDAN - Ruth Mianty Br Sagala; Sartika Sari, SS, M.Hum.,; Hilda Septriani, SS, M.Hum., (English Language Teaching Prima Journal (ELT), 2025)
This study aims to examine the gender construction depicted in the legend of Putri Hijau in Siberaya Village and explore its relevance as a teaching material at SMP Negeri 8 Medan. This legend tells the story of Putri Hijau who has a beautiful face and is considered to have mystical powers that come from gods and goddesses. Her struggle to maintain her dignity as a woman who is forced to marry a king. The research process was carried out through interviews with individuals who have a relationship with the legend. The method used is descriptive with a qualitative approach. The findings of the study indicate that the legend of Putri Hijau depicts women as strong and brave figures. In addition, this legend emphasizes the importance of gender equality towards the role of women in social life. This study concludes that the legend of Putri Hijau in Siberaya Village is relevant to be used as a teaching material at SMP Negeri 8 Medan to increase students' awareness and understanding of gender equality and the role of women in society and increase students' knowledge of the values ​​contained in a legend. Keywords: Gender, Legend, Women, Feminist, Patriarchy, Teaching Materials